Synthesis, crystal structures and Jack bean urease inhibitory activity of copper(II) complexes with 4-bromo-N′-(2-hydroxy-5-methoxybenzylidene)benzohydrazide. Issue 3 (1st February 2017) - Wang, Jing; Qu, Dan; Lei, Jin-Xian; You, Zhonglu
Abstract: A new hydrazone 4-bromo- N′ -(2-hydroxy-5-methoxybenzylidene)benzohydrazide (HL) was prepared and characterized by infrared and UV–vis spectra, as well as single-crystal X-ray diffraction. With the hydrazone as ligand, two new copper(II) complexes were prepared, [Cu2 L2 (NCS)2 ]·4H2 O (1 ) and [CuBrL]·CH3 OH (2 ). The complexes were characterized by infrared and UV–vis spectra, and single-crystal X-ray diffraction. The Cu in1 is in a square pyramidal coordination geometry and that in2 is in a square planar coordination geometry. The two complexes show effective Jack bean urease inhibitory activity, with IC50 values of 23.5 and 2.7 μM, respectively. A molecular docking study of2 with the urease was performed. The relationship between the structure and urease inhibitory activity indicated that copper complex with square planar coordination is a better model for urease inhibition. Abstract :